RATIONALIZATION OF ENERGY CONSUMPTION IN PUBLIC BUS TRANSPORTATION - CASE OF THE CENTER OF OUM AL-BOUGHI CITY - Gherabi Nedjla; Ketfi Soltana; Bousmaha Hadjer (International Journal of Innovative Technologies in Social Science, 2024)
The city of Oum El-Bouaghi has great importance due to its good and strategic location, which has given it a prominent place in the economic movement. It is considered a transit zone between the north and the south via National Road No. 10 and National Road No. 32. All these advantages can help the city to move the wheel of sustainable development forward. Public urban transportation is a vital artery in the urban system, as it plays a fundamental role in structuring the urban area and circulating daily movement with all its various activities. Accordingly, it is necessary to activate a traffic system that relies on energy conservation techniques to mitigate the problems that negatively affect the activity of individuals and hinder the functional movement of cities, in addition to other problems that are harmful to health due to air pollution. This can be done by encouraging the clean public urban transportation sector within the urban environment. On this basis, the topic of our research revolves around the rationalization of energy consumption in public transportation in the city of Oum El-Bouaghi by buses. It is a means to confront the many challenges facing the latter, such as the continuous increase in population density and the increase in the rate of daily movements, which results in many traffic problems. The phenomenon of traffic congestion is at the top of these problems, as well as the noise resulting from heavy traffic, and the excessive consumption of fuel. Therefore, it is necessary to work hard to ensure the operation of sustainable public urban transportation.